610 EMERGING TRIGGERS OF ARRHYTHMIC EVENTS IN REMOTE MONITORED PATIENTS. (15th December 2022) - Giordano, Federica; Telesca, Alessandro; Ballacci, Federico; Flore, Francesco; Scacciavillani, Roberto; Bencardino, Gianluigi; Perna, Francesco; Pinnacchio, Gaetano; Spera, Francesco Raffaele; Pelargonio, Gemma; Antonio Montone, Rocco; Niccoli, Giampaolo; et al.
Abstract: Background and aims: Worldwide, air pollution is the fourth leading cause of death. Both brief and long-term exposures to air pollution have been associated with marked increases in cardiovascular-related morbidity and mortality. Previous studies have focused on the short-term influence of particulate pollutants on ventricular arrhythmia (VA) development, primarily expressed as 24-hour Holter ECG monitoring arrhythmic burden or as presentation as life-threatening ventricular arrhythmias. The aim of our study was to investigate the association between air pollutant exposure and VA burden in remotely-monitored patients. Methods: We enrolled retrospectively 86 patients carriers of implantable cardioverter-defibrillators (ICD), loop recorders (ILR) or pacemaker devices with remote monitoring via Carelink TM Medtronic or Merlin.net TM PCN Abbott softwares. Intracavitary and ILR tracings were reviewed by EP personnel at our centre to define VA burden and the number of appropriate shocks and ATPs occurred in 2021. Demographic and clinical characteristics (e.g. cardiovascular history, ejection fraction, smoking, antiarrhythmic drugs (AADs)) were collected through telephone interviews. Each patient's residential and working address were used to obtain information on pollutant exposure in the years 2017-2021 in terms of annual mean concentrations of PM10, PM2.5, ozone, sulfur dioxide, carbon dioxide, carbon monoxide and benzene, as determined by European Environmental Agency air quality reports. The primary endpoint was a composite of ventricular fibrillation, sustained and nonsustained ventricular tachycardia, appropriate ATP or shocks in patients with various levels of air pollutants exposure. Results: Of 86 patients (58 male, mean age 63.2±18.7 years) enrolled in this study, 44 (51.6%) had received an ICD, 32 of whom (37.2%) with a primary prevention indication. 31 patients (36.1%) had been receiving at least one AAD. History of coronary artery disease (CAD) was present in one third of the study population and baseline mean EF was 49.8±13.8%. VA events occurred in 17 patients (19.8%), all with a significantly lower baseline EF (40.3±12.2% vs 51.5±13.5% p=0.005). Average mean values of benzene concentration in the previous 4 years were significantly higher in patients suffering from a VA event (1.64±0.82 μg/m3 vs 1.12±0.48 μg/m3, p=0.001), as were PM2.5 values (11.64±1.98 vs 10.74±1.28 μg/m3, p=0.023). A weak but positive correlation was found between median PM2.5 concentration, benzene and VAs (p=0.023, p=0.001 respectively). A multivariate regression model was built, including long-term exposure to benzene and PM2.5 and baseline EF, and it would explain 29.8% of the variance in VAs, correctly classifying 78.1% of cases. Conclusions: This study was the first to evaluate the relationship between long-term exposure to a wide array of air pollutants and VAs in a European population. In our sample, we found a weak but significant correlation between a higher chronic exposure to benzene and recorded VA events. Possible mechanisms may include oxidative stress and a direct, nonspecific membrane action due to benzene lipophilic properties. Hence, we highlighted the possible role of outdoor benzene exposure in ventricular arrhythmogenesis for the first time, a finding that requires validation through subsequent studies aimed at elucidating the role of air pollution as a ubiquitous, potentially modifiable, population-based risk factor.